Acetylcholinesterase inhibition and antibacterial activity of Mondia whitei adventitious roots and ex vitro-grown somatic embryogenic-biomass - Ponnusamy Baskaran; Aloka Kumari; Bhekumthetho Ncube; Johannes Van Staden (Frontiers Media S.A., 2016)
Mondia whitei (Hook.f.) Skeels is an important endangered medicinal and commercial plant in South Africa. In vitro propagation systems are required for biomass production and bioactivity analysis to supplement wild resources/stocks. Adventitious roots from somatic embryogenic explants using suspension culture and ex vitro-grown plants produced via somatic embryogenesis were established using different plant growth regulator treatments. The adventitious root biomass and different parts of ex vitro-grown and mother plants were used to investigate the potential for acetylcholinesterase (AChE) and antibacterial activities. Adventitious roots derived from 2.5 µM indole-3-acetic acid (IAA) treatments and ex vitro-grown plants derived from meta-topolin riboside (mTR) and IAA treatments gave the best AChE and antibacterial activities. The in vitro-established M. whitei and ex vitro biomass have comparable ability to function as inhibitors of acetylcholinesterase and antibacterial agents, and can be used as potent bioresources in traditional medicine